Pattern Formation During Animal Development - Melton, D. A. (Science (American Association for the Advancement of Science), 1991)
At the beginning of this century, embryologists defined the central problems of developmental biology that remain today. These questions include how differentiated cells arise and form tissues and organs and how pattern is generated. In short, how does an egg give rise to an adult? In recent years, the application of molecular biology to cmbryological problems has led to significant advances and recast old problems in molecular and cellular terms. Although not necessarily comprehensive, this idiosyncratic review is intended to highlight selected findings and indicate where there are important gaps in our knowledge for those less than familiar with developmental biology.